Analisis Perawatan Self Contained Breathing Apparatus di Bandar Udara Kualanamu - Harliansyah Hasibuan; Tiara Nugrahayani; Lina Rosmayanti (LPPM Politeknik Pratama, 2025)
The Self-Contained Breathing Apparatus (SCBA) is a vital safety device used by Aircraft Rescue and Firefighting (ARFF) personnel during rescue and firefighting operations at the airport. This study aims to analyze the SCBA maintenance process to ensure equipment reliability and personnel safety at Kualanamu International Airport Medan. This research employs a qualitative descriptive method, with data collection techniques including direct observation, in-depth interviews, and field documentation conducted during the author’s On the Job Training (OJT) from October 2024 to February 2025. Research instruments such as interview guides and observation sheets were utilized to identify weaknesses in the SCBA maintenance system. The results reveal that the SCBA maintenance process is not yet optimal, as indicated by the absence of a specific checklist and standardized inspection procedures for each SCBA component. Furthermore, the location of the clean air refill compressor, which is placed near the vehicle parking area, poses a risk of air contamination within the SCBA cylinders. Additionally, the number of available SCBA units does not meet the minimum standards stipulated in Regulation PR 30 of 2022. The proposed solutions in this study include the development of a standardized inspection logbook, procurement of SCBA units with uniform specifications, and the construction of a dedicated room for compressor placement.